1991
DOI: 10.1038/bjc.1991.261
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks in thyroid cancer patients

Abstract: Summary Cancer risks were studied in 834 thyroid cancer patients given 'l'I (4,551 MBq, average) Iodine-131 was first described in medical practice more than 40 years ago and is still frequently used in the diagnosis and treatment of thyroid disorders (Hamilton & Lawrence, 1942;Hertz & Roberts, 1942).In cases of nuclear explosions or reactor accidents large amounts of 131I could be spread over vast areas causing a potential hazard to human beings (Becker, 1987). Data on risks associated with radioactive iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
30
1
5

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 15 publications
7
30
1
5
Order By: Relevance
“…In addition, we identified a strong relationship between the cumulative activity of 131 I and risk of bone and soft-tissue cancer, colorectal cancer, and salivary gland cancer. The increased incidence of SPM seen in the present study and previously reported (Tucker et al, 1985;Hall et al, 1990Hall et al, , 1991Dottorini et al, 1995;Edhemovic et al, 1998) could also be related to an increased medical surveillance, common aetiological factors including hereditary factors, or misclassified metastases. Although increased medical surveillance could contribute to an earlier detection of cancers with a long latency, it could hardly explain the excess of leukaemia and of solid cancers with a poor prognosis and a rapid evolution.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In addition, we identified a strong relationship between the cumulative activity of 131 I and risk of bone and soft-tissue cancer, colorectal cancer, and salivary gland cancer. The increased incidence of SPM seen in the present study and previously reported (Tucker et al, 1985;Hall et al, 1990Hall et al, , 1991Dottorini et al, 1995;Edhemovic et al, 1998) could also be related to an increased medical surveillance, common aetiological factors including hereditary factors, or misclassified metastases. Although increased medical surveillance could contribute to an earlier detection of cancers with a long latency, it could hardly explain the excess of leukaemia and of solid cancers with a poor prognosis and a rapid evolution.…”
Section: Discussionsupporting
confidence: 71%
“…The excess of colorectal cancer was previously evidenced only in the French cohort (de Vathaire et al, 1997), and the excess of salivary gland cancer was found in the Swedish (Hall et al, 1991) and Italian (Dottorini et al, 1995) cohorts. In contrast, the excess of bone and soft-tissue cancers following 131 I administration has not been previously reported.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations